Five Days Granulocyte Colony-Stimulating Factor Treatment Increases Bone Formation and Reduces Gap Size of a Rat Segmental Bone Defect: A Pilot Study - Herrmann, Marietta; Zeiter, Stephan; Eberli, Ursula; Hildebrand, Maria; Camenisch, Karin; Menzel, Ursula; Alini, Mauro; Verrier, Sophie; Stadelmann, Vincent A. (Frontiers in Bioengineering and Biotechnology, 2018)
Bone is an organ with high natural regenerative capacity and most fractures heal spontaneously when appropriate fracture fixation is provided. However, additional treatment is required for patients with large segmental defects exceeding the endogenous healing potential and for patients suffering from fracture non-unions. These cases are often associated with insufficient vascularization. Transplantation of CD34+ endothelial progenitor cells (EPCs) has been successfully applied to promote neovascularization of bone defects, however including extensive ex vivo manipulation of cells. Here we hypothesized, that treatment with Granulocyte colony-stimulating factor (G-CSF) may improve bone healing by mobilization of CD34+ progenitor cells into the circulation, which in turn may facilitate vascularization at the defect site. In this pilot study, we aimed to characterize the different cell populations mobilized by G-CSF and investigate the influence of cell mobilization on the healing of a critical size femoral defect in rats. Cell mobilization was investigated by flow cytometry at different time points after five consecutive daily G-CSF injections. In a pilot study, bone healing of a 4.5 mm critically-sized femoral defect in F344 rats was compared between a saline-treated control group and a G-CSF treatment group. In vivo micro computed tomography and histology were applied to compare bone formation in both treatment groups. Our data revealed that leukocyte counts show a peak increase at the first day after the last G-CSF injection. In addition, we found that CD34+ progenitor cells, including EPCs, were significantly enriched at day 1, and further increased at day 5 and day 11. Upregulation of monocytes, granulocytes and macrophages peaked at day 1. G-CSF treatment significantly increased bone volume and bone density in the defect, which was confirmed by histology. Our data show that different cell populations are mobilized by G-CSF treatment in cell specific patterns. Although in this pilot study no bridging of the critically-sized defect was observed, significantly improved bone formation by G-CSF treatment was clearly shown.